The Political Culture of Exclusivity in the Republic of Serbia During the Student Blockades of 2024/2025: An Essay on Cultural Fascism - Radenović, Sandra S. (Collection of Papers of the Faculty of Philosophy in Priština, 2026)
The aim of this research is to examine the characteristics of political culture in the Republic of Serbia during the student blockades (2024/2025), using as a case study the reactions within the author’s professional and family environment to her visit to Pionirski Park and to the group of students “who want to learn.” The study addresses two issues that may shape the dominant features of political culture at both micro and macro levels: (1) the accuracy of information concerning the author’s statement during the visit to Pionirski Park; and (2) the level of understanding among members of the author’s professional and family environment regarding the professor–student relationship. Methodologically, the research takes the form of a case study and employs observation with participation, the biographical method, content analysis, and interviews. The author identifies exclusivity as the central characteristic of political culture present at both micro and macro levels, particularly in public discourse during the student blockades. The findings confirm exclusivity as the dominant feature of political culture, particularly in public discourse during the ongoing social and political crisis in the Republic of Serbia associated with the student blockades of 2024/2025. Exclusivity is analyzed through specific examples that reveal elements of cultural fascism, racism, and speciesism. It is further accompanied by collectivism, single-mindedness, and totalitarian tendencies in the thinking and actions of political actors who perceive their opponents not only as political adversaries but also as members of inferior cultural groups, races, or even species. This research raises the urgent question of how exclusivity, as a dominant characteristic of political culture in contemporary Serbian society, can be effectively reduced.